2012
DOI: 10.5539/sar.v1n1p26
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting Antioxidant Capacities and Health-Enhancing Phytonutrient Contents of Southern Highbush Blueberry Wine Compared to Grape Wines and Fruit Liquors

Abstract: Blueberry wines may have a multitude of health benefits, but few studies have quantified the health-enhancing antioxidants, total phenols, anthocyanins and flavonoids in blueberry wines, especially the Southern highbush blueberry wine, in comparison to grape wines and fruit liquors. This study was initiated to fill such a gap by measuring the antioxidant capacity and key phytonutrients of Southern highbush blueberry wine as compared to red, Rose and white wines and fruit liquors. The Oxygen Radical Absorbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Especially in the USA and Canada, the production of wine from blueberries has a great economic relevance. Vaccinium corymbosum , Vaccinium ashei , and Vaccinium angustifolium are the species mainly used for winemaking in these countries. Corresponding wines have been investigated regarding phenolic compounds and antioxidative capacity. The antioxidant capacity of Canadian blueberry wine was shown to be much higher compared to the initial juice .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially in the USA and Canada, the production of wine from blueberries has a great economic relevance. Vaccinium corymbosum , Vaccinium ashei , and Vaccinium angustifolium are the species mainly used for winemaking in these countries. Corresponding wines have been investigated regarding phenolic compounds and antioxidative capacity. The antioxidant capacity of Canadian blueberry wine was shown to be much higher compared to the initial juice .…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, this effect is attributed to both an increase in the phenolic content and changes in the phenolic profile. Others highlighted the high antioxidative capacity of American blueberry wine compared to conventional red wine. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yams are rich in polyphenols ( Aarti et al, 2013 ), which play an essential role in antioxidant and biological activity ( Kalt et al, 1999 ). Studies have indicated that polyphenolic compounds are positively correlated with antioxidant capacity ( Yang et al, 2012 ) and that the antioxidant activity of flavonoids can eliminate reactive oxygen species and terminate the chain reactions of free radicals ( Arora, Nair & Strasburg, 1998 ). Moreover, purple yams contain abundant anthocyanins, which have the antioxidant capacity to inhibit lipid peroxidation, resist the attack of free radicals, diminish low-density lipoproteins (LDLs), and reduce the occurrence of cardiovascular diseases ( Wang, Cao & Prior, 1997 ); thus, the antioxidant substances that exist in yam tubers have potential for development and utilization in medicine ( Teixeira et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Commercial blueberry species used for winemaking originate from the genus Vaccinium , which contains numerous volatile organic compounds and contributes to olfactory sensation ( Sater et al, 2020 ). As a high value-added product, blueberry wine was reported to be a rich anthocyanin source ( Cho et al, 2004 ) and has excellent antioxidant activity ( Johnson and de Mejia, 2012 ), exhibiting potential health-enhancing benefits ( Yang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%